Treatment of Generalized Anxiety Disorder with Gabapentin - Matej Markota; Robert J. Morgan (Case Reports in Psychiatry)
Gabapentin is frequently used in the treatment of anxiety disorders. However, there are no randomized controlled trials on the effectiveness of this medication in generalized anxiety disorder (GAD), and there are only a few case reports. We present a case of a 59-year-old female with a psychiatric history of GAD. The patient discontinued benzodiazepines after more than 7 years of daily treatment which led to rebound anxiety, benzodiazepine withdrawal symptoms, and suicidal ideation. She was psychiatrically hospitalized and started on gabapentin. Over the next 10 months of outpatient follow-up, she attempted to taper off gabapentin due to personal preference to limit medications. During this time, we observed a clear dose-response pattern of gabapentin on GAD symptoms. In the absence of controlled studies, these findings may offer important information about the effectiveness of gabapentin in GAD.